Water stress, vermiculite and cultivars I. Effect on rice yield - Stone, Luis Fernando; Libardi, Paulo Leonel; Reichardt, Klaus (Pesquisa Agropecuaria Brasileira, 2014)
The effect of four irrigation levels and two vermiculite treatments on the yield of three rice cultivars (Oryza sativa L.) (IAC 47, IRAT 13 and IET 1444) was studied in a greenhouse experiment. The treatments included the irrigation levels corresponding to 55, 70, 85 and 100% of maximum evapotranspiration with and without vermiculite incorporation in the soil at 10% concentration on volume basis. The incorporation of vermiculite into the soil increased the pH, CEC, exchangeable cation (Ca, Mg and K) concentration and decreased the exchangeable aluminium concentration. It did not affect the grain yield nor the water use efficiency (WUE). Under conditions of water stress the cultivar IRAT 13 exhibited greater grain yield stability, WUE, harvest index (HI) and root/shoot ratio as compared to the other cultivars, indicating that it possesses better adaptation to water stress. The water stress decreased the number of filled grains per panicle, grain weight, grain yield, total dry matter yield, plant height, HI, WUE and increased the percentage of unfilled grains, growth duration and root dry matter yield. Further, while the root/shoot ratio of the upland cultivars increased, it did not significantly affect that of the lowland cultivar.